1998
DOI: 10.1007/s004210050468
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone responses to continuous and intermittent exercise in females under oral contraceptive therapy

Abstract: In this study we investigated the effect of oral contraceptive (OC) use (OCU) and non-use (OCNU) on growth hormone (GH) responses to exercise in the same females (n = 7, age 22-31 years) during the normal course of OC therapy. Continuous (60% maximum oxygen consumption, VO2max for 20 min) and intermittent exercise (>80% VO2max) protocols of equal total duration, and similar external work were performed during phases of OCNU (days 3-5 of the menstrual cycle) and OCU (days 7-11). Levels of GH, lactate, 17 beta-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…Consistent with Felsing's findings (Felsing et al 1992), these data revealed an absolute increase in GH levels of 9.5 ngAEml )1 for the 10-min exercise bout on the cycle ergometer, while it demonstrated an absolute increase of 5.7 ngAEml )1 on the treadmill. This increase in GH levels is similar to increases in GH seen in exercise protocols using a single bout of exercise of longer duration in women (Bunt et al 1986;Wideman et al 1999), while these increases appear to be somewhat smaller than what Bernardes and Radomski (1998) found in women on oral contraceptives. The earlier work by Felsing showed no significant increase with 1 and 5 min of exercise.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Consistent with Felsing's findings (Felsing et al 1992), these data revealed an absolute increase in GH levels of 9.5 ngAEml )1 for the 10-min exercise bout on the cycle ergometer, while it demonstrated an absolute increase of 5.7 ngAEml )1 on the treadmill. This increase in GH levels is similar to increases in GH seen in exercise protocols using a single bout of exercise of longer duration in women (Bunt et al 1986;Wideman et al 1999), while these increases appear to be somewhat smaller than what Bernardes and Radomski (1998) found in women on oral contraceptives. The earlier work by Felsing showed no significant increase with 1 and 5 min of exercise.…”
Section: Discussionsupporting
confidence: 74%
“…Oral contraceptive use has been shown to be related to these higher resting GH concentrations (Bonen et al 1983). Oral contraceptive users have been shown to have an appropriate GH response to exercise (Bemben et al 1992;Bernardes and Radomski 1998;Bonen et al 1983) and in our study 10 min of exercise also stimulated a significant GH response. However we found a decline in GH levels with subsequent exercise bouts and have no explanation for this since it deviates from what is reported to occur in men (Kanaley et al 1997).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A progesterona não respondeu de forma significativa quanto à fase do CM ou o tipo de exercício. Essa aumentou durante os dois tipos de exercício em todas as condições do ciclo e retornou aos valores de pré-exercício 60 minutos depois de cessado o mesmo 17 .…”
Section: Discussionunclassified